Biodegradable polymer nanocomposites for ligament/tendon tissue engineering - Silva, M. (2020)
Ligaments and tendons are fibrous tissues with poor vascularity and limited regeneration capacity. Currently, a ligament/tendon injury often require a surgical procedure using auto- or allografts that present some limitations. These inadequacies combined with the significant economic and health impact have prompted the development of tissue engineering approaches. Several natural and synthetic biodegradable polymers as well as composites, blends and hybrids based on such materials have been used to produce tendon and ligament scaffolds. Given the complex structure of native tissues, the production of fiber-based scaffolds has been the preferred option for tendon/ligament tissue engineering. Electrospinning and several textile methods such as twisting, braiding and knitting have been used to produce these scaffolds. This review focuses on the developments achieved in the preparation of tendon/ ligament scaffolds based on different biodegradable polymers. Several examples are overviewed and their processing methodologies, as well as their biological and mechanical performances, are discussed.